PHYSIOLOGICAL CHANGES IN PARTICIPANTS OF AN ULTRAMARATHON IN SUBARCTIC CLIMATE - M. Steinach; O. Opatz; Stahn, A; Gunga; M.A. Maggioni (2014)
Introduction The Yukon Arctic Ultra (YAU) is an ultramarathon in the Yukon-Territory of Canada taking place during February. We assessed changes in participants entering the 690km footrace and evaluated energy expenditure (EE), energy intake (EI), energy deficit (ED), body weight (BW) and composition (fat mass FM, fat-free mass FFM), sleep parameters (sleep time ST, REM-sleep RS, deep-sleep DS) and heart rate variability HRV (pNN50 and lowfrequency to high-frequency ratio LF/HF). We hypothesized that high levels of physical exertion in the extremely cold environment would lead to changes in these parameters. Material & Methods N=4 of n=6 volunteers finished and were included in the analysis. BW, FM, FFM were measured using a scale and the bio-impedance-analysis. EI, ED were estimated using food protocols. EE, ST were measured using the SenseWear-actimeter continuously and RS and DS using the Zeo-Sleep-device at distinctive nights. HRV (pNN50, LF/HF) was evaluated using the Polar-monitor RS800CX and beat-to-beat analysis. Resulting data were statistically analyzed using respective statistical software. Results The evaluation revealed high rates of daily EE (an average of 4.5 MET/d with peak values of 38,000 kJ/d). We also found a considerable ED: only 44% of the EE was covered by EI (p<0.001). Considerable changes in BW, FM, FFM occurred: participants lost an average 6.2 kg of BW (p<0.001) with a maximum loss of 7.9 kg. Regarding body composition, there was an initial loss in FM (p<0.001) and in progression a loss in FFM (p=0.052). The average FM loss was 3.9 kg and 2.3 kg in FFM (=27.9% from starting-FM, 3.4% from starting-FFM). We found a sleep deficit at the start and end of the race; however, ST decreases were not significant (p=0.05). There were changes in the sleep phases: a decrease in RS after the beginning (p=0.005) and increase in DS after the end of the race (p=0.386). Analysis of HRV revealed a decrease in the pNN50 (p=0.429) and a significant decrease in the LF/HF (p=0.035). Discussion ...